EVALUATION OF SOCIAL MEDIA INFLUENCE ON PUBLIC ADMINISTRATION - Nasir Khan; Dr. Bakht Zaman; Dr. Sajjad Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
Social media has offered public administration a rapid and revolutionary opportunity to utilise technology, interact with the public and stakeholders, and enhance transparency in governance. This paper aims to comprehend the complex and changing elements of social media utilisation in public administration. The main focus is on the practical application of the technology for communication engagement, decision-making in a democratic society, and crisis management. The analysis unequivocally shows that social media has both informative and onerous effects on public administration. These entail the direct engagement of the government with citizens by integrating real-time tweets into public communication. The study emphasises the importance of improving fact-checking mechanisms and media literacy in order to effectively mitigate the risks. This study initially conducts a literature review to ascertain the trends and patterns in the utilisation of social media in public administration. Subsequently, a thorough examination of the literature is conducted, with a specific emphasis on social media in the field of public administration. Therefore, it highlights the significance of implementing more robust regulatory mechanisms and effective management of social networking platforms, which involves the establishment of clearly defined policies for the use of social media. Hence, the aforementioned observations suggest that social media has the potential to enhance communication and facilitate the dissemination of public sector initiatives. Nevertheless, it is imperative to establish efficient regulation to address emerging risks, such as unauthorised divulgence of personal data or the dissemination of misinformation. The current study also examined the impact of social media on public policy, demonstrating that policy makers utilise it as a means to evaluate public sentiment and adjust their approaches accordingly. In the field of crisis communication, social media plays several distinct roles, such as facilitating the spread and organisation of crucial information among the general population during times of emergencies. The strong relation between social media and public administration highlights the constantly evolving process of governance in the modern digital era.